Therapeutic Communication in Providing Psychological and Social Support to Cancer Patients for the 'Surabaya Hebat' Cadre - Septia Iswidyanti, Shinta; Surjaningrum, Endang R. (Journal La Medihealtico, 2024)
This study aims to enhance the knowledge capacity of Surabaya Hebat Cadres through training in social and psychological support for cancer patients and to improve the palliative care program for cancer patients. The designed community intervention, "Therapeutic Communication Training in Psychological and Social Support for Cancer Patients," is expected to improve the cadres' communication skills, enabling them to provide more effective support. This study employs a participatory descriptive design involving active participant engagement at every stage of the training, with a focus on evaluating the andragogic-based training program. The sample consists of all Surabaya Hebat Cadres in RW 3 Dukuh Setro Village, totaling 28 individuals, with data collected through participatory observation and questionnaires. Data analysis techniques include descriptive quantitative analysis using descriptive statistics and paired sample T-Test for the questionnaires. The results show that psychoeducation on therapeutic communication effectively improves the knowledge of Surabaya Hebat Cadres and can be integrated with the palliative program at Puskesmas. The improvement in cadres' communication skills contributes to more effective support for cancer patients, thereby enhancing their quality of life.